Fatigue life and rutting performance modelling of nanosilica/polymer composite modified asphalt mixtures using Weibull distribution - Bala, N. (Taylor and Francis Ltd., 2018)
This study has investigated the fatigue and rutting performance of composite polyethylene (PE) and polypropylene (PP) asphalt mixtures with the addition of nanosilica particles (NS). In this study, a composite modified asphalt binder was prepared usingPE and PP with NS in a concentration of 1â4 by weight of bitumen. A flexural beam fatigue test using four-point flexural beam fatigue test was conducted. A Wessex wheel tracking test was also conducted to estimate the rutting deformation of the mixtures. Weibull distribution was applied to evaluate the fatigue life of the two composite mixtures at different strain levels. A parametric survival analysis was utilised to compare the reliability of the composites. Also, a Weibull failure rate function was used to fit the experimental Wessex wheel tracking rut depth results. The results showed that the fatigue life of the composite mixtures at all strain levels complied with a two-parameter Weibull distribution with a statistical coefficient of determination greater than 0.9. The survival analysis showed that the PP composites had higher reliability at all strain levels. Furthermore, a good correlation was observed between the fitted Weibull failure rate function and the experimental rut depth obtained from the Wessex wheel tracking test. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group